1991
DOI: 10.1111/j.1471-4159.1991.tb02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct, Developmentally Regulated Brain mRNAs Direct the Synthesis of Neurotransmitter Transporters

Abstract: The Xenopus laevis oocyte expression system was utilized to define developmental and structural properties of neurotransmitter transporter mRNAs and the pharmacological characteristics of encoded carriers independent of the complexities of brain tissue preparations. Poly(A)+ RNA from dissected brain regions of neonatal and adult rats was microinjected into Xenopus oocytes and the expression of Na(+)-dependent neurotransmitter transporters determined 48 h later. Transport studies conducted with oocytes injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 73 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…However, after cloning several glycine transporters, there is no evidence for a 2.4 kb mRNA coding for a glycine transporter. Taking together the size and localization of the 4 kb mRNA described previously (Blakely et al, 1991a), it is likely that this same gene product codes for GLYT1. However, this study failed to detect the 8.0 kb band corresponding to the GLYT2 mRNA.…”
Section: Discussionmentioning
confidence: 78%
“…However, after cloning several glycine transporters, there is no evidence for a 2.4 kb mRNA coding for a glycine transporter. Taking together the size and localization of the 4 kb mRNA described previously (Blakely et al, 1991a), it is likely that this same gene product codes for GLYT1. However, this study failed to detect the 8.0 kb band corresponding to the GLYT2 mRNA.…”
Section: Discussionmentioning
confidence: 78%
“…Xenopus laevis Oocyte Expression-X. laevis were purchased from Xenopus (Ann Arbor, MI) and oocytes were dissected and prepared as described previously (26 Protease Protection Assay-Proteinase K (Boehringer Mannheim) was added to aliquots of oocyte homogenates (0.2 mg/ml final) in the presence or absence of 1% Triton X-100 and incubated on ice for 1 h. Protease was inactivated by addition of 10 mM phenylmethylsulfonyl fluoride (Sigma) in Me 2 SO, dilution with 10 volumes of 1% SDS, 0.1 M Tris, pH 8.0, and boiling for 5-10 min. Samples were diluted with 4 volumes of 1.25 ϫ RIPA buffer (187.5 mM NaCl, 1.25% Triton X-100, 1.25% deoxycholate, 62.5 mM Tris, pH 8.0, 2.5 mM EDTA, 0.125% SDS) and set at 4°C with rocking ϳ12-16 h. Samples were centrifuged at 14,000 ϫ g for 15 min and proteins immunoprecipitated from the supernatant as described below.…”
Section: Materials-[mentioning
confidence: 99%
“…Regional enrichment of transporter mRNAs followed well the distribution of soma predicted to synthesize each carrier. In addition, pharmacologic sensitivities of oocyte-expressed transporters were similar (Blakely et al 1991a) if not identical to those observed in brain membrane preparations (table 1). Using mRNA prepared from different brain regions during development, Blakely and colleagues (1991a) revealed a postnatal rise in Glu, GABA, and Gly transporter transcript abundance paralleling the postnatal rise in brain transport activity for these substrates.…”
Section: Expression Of Neurotransmlter Transporters In Xenopus Laevismentioning
confidence: 65%